DEVELOPMENT OF EDI (ELECTRONIC DATA INTERCHANGE) IN START-UP COMPANY DATA INTEGRATION PROCESS TO EFFECTIVE OPERATIONAL COSTS FOR MICRO AND MEDIUM ENTERPRISES IN JAKARTA - Asyari Asyari (CV ODIS, 2021)
Communication technology has a contribution in business capable of transforming data and information to all parties in need quickly and accurately. If the information reaches the user quickly then decision-making will also be fast. The development of internet technology and the application of the World Wide Web contribute to the development of electronic commerce (EC). EC is the use of all types of electronic networks, including the internet to provide services online. The purpose of this study was to conduct a descriptive study of the functions of EDI (Electronic Data Interchange) in application software used by MSMEs in assisting administration and business development. The results of the study illustrate that EDI has an influence on reducing marketing costs, HR costs, and operational costs as well as increasing operating profits for several MSMEs that have used online marketing media such as Tokopedia, Lazada, Bukalapak.com, and Shopee with the help of application software, but a small proportion have not used it.